Pannonian Production of Thin-Walled Pottery from Mursa: Campus 2001–2015 - Šuljug, Mirna; Filipović, Slavica (Rei Cretariae Romanae Fautorum Acta, 2022)
In the period from 2001 to 2015, in the area of the present day University Campus in Osijek (Croatia), rescue archaeological excavations of Roman Mursa were conducted. Thin–walled pottery found in these excavations is represented by a small number of finds in comparison to other classes of pottery, however, they present characteristics by which is possible to determine affiliation to certain major production centers. Under their influences, potters in Pannonia also developed their own local production which follows the usual template in forms and decoration. In the period from the second half of 1st to the first half of 2nd century AD the most common vessels are the ones that imitate forms of Italian production. By the later period, during the 2nd and 3rd century AD, new forms of thin-walled cups and beakers had taken over the local market. During this time they were also produced in Mursa, which is confirmed by the numerous findings from pottery kilns. These new forms became the common types of drinking vessels and completely took over the local market, slowly pushing earlier Italic forms out of use.